Factors affecting the demand for higher education in medical universities in Iran - Batool Shafiezad Abkenar; Seyed Nematullah Mousavi; Mahdi Kamali; Mohammad Mohebbi (Shahid Beheshti University of Medical Sciences, 2024)
Background: One of the most effective indicators of human capital and social determinants of health is the number of university graduates. Investigating the variables influencing Iran's desire for higher education was the goal of this study. Methods: In this cross sectional study, the Autoregressive Distributed Lag (ARDL) method was used. The questionnaire used in this study included a researcher-made questionnaire to collect information on the target variables of the study. The first stage was using the Banerjee, Dolado, and Mastre approaches to find out if the model had a long-term connection before doing the long-term co-integration test. The t-statistics connected to coefficients inside an interval of the dependent variable served as the basis for this test's execution. The dynamic error correction model (ECM) and the ARDL model's long-term coefficients were retrieved. The Gulpak article model and information from the Central Bank of the Islamic Republic of Iran, the Statistics Center, and other sources were utilized to investigate the variables impacting the demand for higher education in Iran. Results: Factors affecting the demand for higher education include the average free and night tuition, economic growth, employment rate, consumer and producer price indices, government spending on education and the ratio of urban population to the total population. The factors that influence the demand for higher education are government spending in the education sector, consumer price indices, and economic growth indicators. Conclusion: Given the role that human resources play in the creation of human societies, particularly in the health sector, raising the proportion of government spending on education can spur demand for postsecondary education and advance national development.